New insight on the risk profile pertaining to lithium-ion batteries under thermal runaway as affected by system modularity and subsequent oxidation regime. (15th August 2022) - Bordes, Arnaud; Marlair, Guy; Zantman, Aurélien; Herreyre, Sylvie; Papin, Arnaud; Desprez, Philippe; Lecocq, Amandine
Abstract: It is now well established that lithium-ion battery technology is a key electrical energy storage device in the fight against the global warming, helping us to make transportation more sustainable and securing intermittent renewable energy sources. The requirement to keep the thermal runaway (TR) hazard under control is among remaining issues for continuous and sustainable use of lithium-ion batteries. This experimental work brings a new insight on the issue, by performing and analyzing of a series of NMC pouch cell internal short circuit tests reflecting progressively the overall level of integration of such cells when modularly assembled in sub-systems to constitute the full pack. While replicating always the same TR triggering procedure in these experiments, our heat, gas and particle emission analyses reveal that the consequences in terms of chemical (e.g. toxic and corrosive) and thermal threats arising from a default cell running into thermal runaway may greatly vary according of the level of integration mocked up during the abuse test. This work also shows that thermochemical reactions/combustion regimes and their transitions following TR (towards possible flaming combustion or simply ending-up by hot gas degassing) are among key determinants of the whole risk pattern. Graphical abstract: Unlabelled Image Highlights: Experimental contribution towards Thermal Runaway (TR) resilient BEV concept Fail-safe focused lithium-ion battery testing strategy developed Appraisal of modular design of battery pack as a barrier against TR propagation Revealing genuine TR-induced oxidation phenomenology variability Thermal and chemical releases (including particles) following TR determined